DINOFLAGELADOS DE LA FACIES DE MAR ABIERTO DEL SANTONIANO-CAMPANIANO DEL SUR DE LAGO VIEDMA, PROVINCIA DE SANTA CRUZ, ARGENTINA (Ameghiniana, 2013)
A microflora of dinoflagellates recorded from Río Guanaco in its open-sea facies from Chorrilo 10 outcrop (ChlO SM), in Estancia La Herradura, south of Lago Viedrna, is presented. Twenty three species, belonging to 20 genera of high cosmopolitan characteristícs are studied, showing affinities with microfloras from the Grand Banks of Newfoundland, Canada, Australia, and several european contries. The association would belong to the austral counterpart of the ""Willíarns Suite"" created by Lentin & WilJiams (1980) based on Campanian peridiniacean dinoflagelates, which would reflect a temperate paleolatitudinal province of the Northern Hemisphere. The Harland lndex for water salinity = 1.25 would mark a lower than normal saliníty, near the shore line. The most common forms of the studied dinoflagellates are: Hystrichodinium cf. isodiametricum (Cookson & Eisenack ) , Hustrichosphaeropsis ooum Deflandre, and Chlamudophorella rujei Cookson & Eisenack. In less amount: Isabelidinium? acuminatum (Cookson & Eisenack ) and Odontochitina operculata (Wetzel).